2021
DOI: 10.1016/j.scog.2020.100188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a computer-assisted cognitive remediation program for young people with psychosis: A pilot study

Abstract: Background People with psychosis have a range of neuropsychological impairments that impact their functional abilities and rehabilitation outcomes. We designed a Computer-Assisted Cognitive Remediation (CACR) program to help young people with psychosis to restore their cognitive function. The program combines the drill-and-practice approach and the strategic approach to remediation, with sixteen sessions of computerized cognitive training, two sessions of psychoeducation, and four session of coach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…First, results showed a satisfactory adherence rate, with almost 70% of the participants completing the entire course of the protocol and adhering to over 80% of the prescribed sessions and outcome measures, suggesting that subjects did not seem to find the time commitment, the assessments, or the training burdensome. These completion rates are comparable with some studies (15,(28)(29)(30) and in contrast with other ones conducted so far (31), showing a higher attrition rate. Nevertheless, the present study adopted several measures to sustain adherence, mostly by strengthening the relationship with the therapist that has been shown to have a fundamental role in ensuring participants' completion of the training modules (32) and providing social cues to improve patients' self-esteem and motivation, supporting the use of strategies, motivation, or reinforcement and helping to develop metacognition, which is thought to be a key component for improving transfer from cognitive change to functional development (33,34).…”
Section: Discussionsupporting
confidence: 89%
“…First, results showed a satisfactory adherence rate, with almost 70% of the participants completing the entire course of the protocol and adhering to over 80% of the prescribed sessions and outcome measures, suggesting that subjects did not seem to find the time commitment, the assessments, or the training burdensome. These completion rates are comparable with some studies (15,(28)(29)(30) and in contrast with other ones conducted so far (31), showing a higher attrition rate. Nevertheless, the present study adopted several measures to sustain adherence, mostly by strengthening the relationship with the therapist that has been shown to have a fundamental role in ensuring participants' completion of the training modules (32) and providing social cues to improve patients' self-esteem and motivation, supporting the use of strategies, motivation, or reinforcement and helping to develop metacognition, which is thought to be a key component for improving transfer from cognitive change to functional development (33,34).…”
Section: Discussionsupporting
confidence: 89%
“…A more recent multi-outcome meta-analysis by Kambeitz-Ilankovic et al ( 52 ) studied outcomes of CACR alone and CACR with supplementary human guidance, which demonstrated similar outcomes to Grynszpan, with the addition of social cognition, reasoning, and global cognition. Looking to an Asian population, an evaluation on CACR was conducted in Hong Kong and found that CACR improves neurocognition ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, achieving cognitive and functional gains through CRT requires sufficient intensity and consistency of training ( Wykes and Spaulding, 2011 ). In particular, the number of sessions attended appears to be significantly associated with improvements in neurocognition ( Best et al, 2020 ; Vita et al, 2021 ), although attendance at enough sessions alone is not sufficient to guarantee the efficacy of a program ( Mahncke et al, 2019 ; Siu et al, 2021 ). Vita et al (2021) showed that beyond the number of training sessions, the guidance by an active, trained therapist, the development of cognitive strategies, and the integration of CRT into a psychiatric rehabilitation concept are highly significantly associated with the cognition- and functioning-related outcomes of CRT.…”
Section: Introductionmentioning
confidence: 99%